Efektivitas Mata Pelajaran Al-Qur’an Hadis Dalam Meningkatkan Kualitas Membaca Al-Qur’an Di Madrasah Tsanawiyah Aisyiyah Sumatera Utara - Siti Arfah Nasution (Al-Ulum: Jurnal Pendidikan Islam, 2022)
This research is motivated by the results of an analysis conducted by the author at Madrasah Tsanawiyah Aisyiyah, North Sumatra when conducting interviews with the principal that in this madrasa students do not have a special program for learning to read the Qur'an but only when studying the subjects of the Qur'an. hadith. From the results of this analysis, the authors want to review the effectiveness of the Al-Qur'an Hadith subjects in improving the quality of students' reading of the Qur'an. The quality of reading the Qur'an is certainly influenced by the level of students' understanding of the law of good and correct recitation. because, it is an absolute requirement that must be owned in order to be able to read the Qur'an in accordance with the rules. Al-qur'an hadith subjects are compulsory subjects in Madrasahs, especially at the Tsanawiyah Madrasah level. These subjects contain scientific studies regarding the Qur'an and hadith which also specifically discuss the laws of recitation in the learning material. This is in accordance with the characteristics of the Al-Qur'an Hadith subjects set by the Ministry of Religion, namely: first, prioritizing the competence to read and also write the Qur'an or Hadith properly and correctly. Second, they are able to understand the content contained in the Qur'an and Hadith both textually and contextually. Third, implementing the contents of the Qur'an in everyday life